2014
DOI: 10.1177/1098612x14556848
|View full text |Cite
|
Sign up to set email alerts
|

Femoral head and neck excision in cats: medium- to long-term functional outcome in 18 cats

Abstract: Based on the owner-completed questionnaire, cats have good-to-excellent medium- to long-term functional outcome after adequately performed FHNE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 28 publications
0
27
0
2
Order By: Relevance
“…, Tomlinson , Yap et al . ). In the three rabbits treated with the IFS technique, after CRES failure in two cases, results were satisfactory over the long term, but over the short and medium term, mild urine scalding was observed, suggesting an altered leg position and/or lameness of the affected limb.…”
Section: Discussionmentioning
confidence: 97%
“…, Tomlinson , Yap et al . ). In the three rabbits treated with the IFS technique, after CRES failure in two cases, results were satisfactory over the long term, but over the short and medium term, mild urine scalding was observed, suggesting an altered leg position and/or lameness of the affected limb.…”
Section: Discussionmentioning
confidence: 97%
“…A previously reported feline owner-based questionnaire was used and clients were contacted by telephone or post to assess the outcome for the cats treated conservatively for SILF. 18 The questionnaire was adapted from Yap et al 18 to include specific questions regarding long-term urination and defecation abnormalities, but is unvalidated (see the supplementary material).…”
Section: Methodsmentioning
confidence: 99%
“…15 More recently, an owner-based questionnaire has been used to assess outcome in feline surgically stabilised unilateral and bilateral SILFs, 16,17 and feline femoral head and neck excisions. 18 Objective gait analysis using force plates has been reported, but access to this resource is limited and often the data yield can be poor in cats owing to their unwillingness to walk on the lead or be guided. 19 The purpose of this study was to determine the medium-to long-term functional outcome for feline patients treated conservatively for SILF.…”
Section: Introductionmentioning
confidence: 99%
“…Femoral head and neck excision (FHNE) is a commonly performed salvage procedure for the diseased or injured coxofemoral joint in dogs and cats. [1][2][3][4][5][6] In cats, FHNE has been reported for the treatment of capital physeal fractures, coxofemoral luxations, acetabular fractures, osteoarthritis and femoral head and neck fractures. [7][8][9][10][11] The procedure was first developed in humans, called the Girdlestone excision arthroplasty for septic tuberculosis lesions, and was adopted into veterinary medicine decades later in dogs for the treatment of coxofemoral diseases.…”
Section: Introductionmentioning
confidence: 99%
“…4,13 A recent owner-completed questionnaire study based on 18 cats with a minimum of 4 months following FHNE showed that owners perceived the cats to have good to excellent function. 1 However, none of these cats received clinical, radiographic or objective gait evaluation. In a study evaluating 66 dogs and 15 cats with clinical examination and re-radiography average of 4 years postoperatively revealed that functional results were rated as good in 38%, satisfactory in 20% and poor in 42% despite a reported owner satisfaction of 96% with the procedure.…”
Section: Introductionmentioning
confidence: 99%